Pengaruh Minat Baca terhadap Hasil Belajar Pendidikan Pancasila Peserta Didik Kelas V SDN 7 Kampungdalem Tulungagung - Sulistyoningsih Puspitosari; Frita Devi Asriyanti (Universitas Nusantara PGRI Kediri, 2024)
Reading interest is a person's desire for works presented in writing. The purpose of the study was to determine the effect of reading interest on the learning outcomes of students at SDN 7 Kampungdalem Tulungagung. This study was quantitative with an ex post facto type. The sampling technique used purposive sampling based on the class level of students with 40 respondents. The data collection technique used a reading interest questionnaire and a Pancasila education learning outcome test. The data analysis technique used a simple linear regression test to determine the magnitude of the effect of reading interest on the learning outcomes of Pancasila education. The results of the study showed that the average reading interest of students was 69.76 with a high category and learning outcomes of 65.37 with a fairly good category. Based on the hypothesis test conducted, there was a unidirectional and positive influence between students' reading interest and Pancasila education learning outcomes, with a sig. value of 0.000 and a tcount value of 6.711 greater than 2.024 ttable. The magnitude of the relationship between reading interest and learning outcomes is 0.542. Students' reading interest has a 54.2% influence on the learning outcomes of Pancasila education and 45.8% is caused by other factors that were not studied. It is hoped that through this study, it can provide information and references for further research, especially those that examine students' reading interest.